2009
DOI: 10.1177/0017896909339532
|View full text |Cite
|
Sign up to set email alerts
|

‘Eating beans … that is a “no-no” for our times’: Young Cypriots’ consumer meanings of ‘healthy’ and ‘fast’ food

Abstract: Objective To investigate in-depth beliefs and experiences relating to the choice of fast and/or healthy foods from a group of young people living in Cyprus. Design Data for the study were generated from one-to-one qualitative interviews which encouraged the participants to articulate the symbolic value of eating choices in their day-to-day experiences. Participants Twenty five young people (12 male, 13 female) aged between 15 and 17 years from diverse socio-economic backgrounds living in different parts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Young adolescents aged 12-14 years are more likely to heed the behaviour of peers regarding risky activities 81 . Furthermore, adolescents typically have independent spending money and, in countries such as Cyprus, Ireland and the UK, use "fast" and "junk" foods as a marker of adolescent identity 82,83,84,85,86 .…”
Section: The Case For Adolescent Vulnerability To Marketing For Unheamentioning
confidence: 99%
“…Young adolescents aged 12-14 years are more likely to heed the behaviour of peers regarding risky activities 81 . Furthermore, adolescents typically have independent spending money and, in countries such as Cyprus, Ireland and the UK, use "fast" and "junk" foods as a marker of adolescent identity 82,83,84,85,86 .…”
Section: The Case For Adolescent Vulnerability To Marketing For Unheamentioning
confidence: 99%
“…Pressure relating to eating habits was discussed in several studies [40,60,70,71,87,88]. One participant highlighted how “ My friends are all around me eating good [unhealthy] food and I’ll be like, “Oh I’m gonna buy that.…”
Section: Resultsmentioning
confidence: 99%
“…People feel more comfortable buying food from the canteen like everyone else, rather than having home-made food, even if it is healthier. If someone is eating a home-made sandwich, he might think that the others are going to make fun of him ”) [87]. Not only was there pressure to eat unhealthy food, but young people also felt pressured to buy expensive foods as eating cheaper foods might mean “ [peers] give you dirty looks and talk about you to your friends ” [40].…”
Section: Resultsmentioning
confidence: 99%
“…The health of our children is one of the most important investments that we can make. Consistency between recognized nutritional standards, national nutrition goals and practice is regarded as an important goal of public health [36][37][38]. Guerra et al [20] reported that Portuguese children aged 12-48 months have lower values of monounsaturated and n-3 polyunsaturated fatty acids in comparison to young Germans, and concluded that traditional food habits are disappearing, even in countries lining the Mediterranean basin.…”
Section: Discussionmentioning
confidence: 99%